2021
DOI: 10.1111/add.15335
|View full text |Cite
|
Sign up to set email alerts
|

Impact of reducing alcohol consumption through price‐based policies on cancer incidence in Germany 2020–50—a simulation study

Abstract: Background and Aims Alcohol is a major cancer risk factor and contributes considerably to the cancer burden in Germany. We aimed to provide projections of preventable cancer cases under different price-based alcohol policy scenarios.Design A macro-simulation approach was used to estimate numbers and proportions of cancer cases prevented under different price-based alcohol policy scenarios. Setting and participants Published price elasticities for main alcoholic beverages were applied to the mean daily intake o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
8
0
3

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 13 publications
(11 citation statements)
references
References 29 publications
(40 reference statements)
0
8
0
3
Order By: Relevance
“…The bidirectional relationship between lifestyle factors and disease might be systemic and multifaceted, for which lifestyle interventions might have a positive impact on overall health in addition to optimizing the disease-specific outcomes (41,42). As a common additive to beverages, the relation of alcohol and bladder cancer risk was still contradictory though much cancer was linked with alcohol consumption (7,43). Past reviews of epidemiological data on alcohol consumption and bladder cancer risk concluded no association and attributed the moderate increase in risk observed in some investigations to residual confounding by smoking, or to an association between alcohol, coffee, and yet unidentified risk factors for bladder cancer (44,45).…”
Section: Discussionmentioning
confidence: 99%
“…The bidirectional relationship between lifestyle factors and disease might be systemic and multifaceted, for which lifestyle interventions might have a positive impact on overall health in addition to optimizing the disease-specific outcomes (41,42). As a common additive to beverages, the relation of alcohol and bladder cancer risk was still contradictory though much cancer was linked with alcohol consumption (7,43). Past reviews of epidemiological data on alcohol consumption and bladder cancer risk concluded no association and attributed the moderate increase in risk observed in some investigations to residual confounding by smoking, or to an association between alcohol, coffee, and yet unidentified risk factors for bladder cancer (44,45).…”
Section: Discussionmentioning
confidence: 99%
“…While further efforts are needed to increase SBIRT delivery in German PHC settings in the long run, e.g., by financial reimbursement of alcohol management activities [ 53 ], alternatives may be required to reduce alcohol consumption and attributable burden in the short-term. In the light of very low alcohol taxation rates, including no taxes for wine [ 54 ], there is a large untapped potential in increasing retail prices for alcoholic beverages, which was demonstrated in two recent modeling studies [ 55 , 56 ]. Evidence from Lithuania and Great Britain, for example, demonstrates the impact that policies targeting alcohol prices can have in reducing consumption and harm [ 57 60 ].…”
Section: Discussionmentioning
confidence: 99%
“…Our analyses arrive at similar conclusions as recent work in other countries. Gredner et al (2020) looked into the possibility of price-based policies on cancer incidence, and concluded that increases in the price of alcoholic beverages will result in substantial decreases in cancer incidence. Similarly, Rovira and colleagues modelled taxation increases in four countries in the WHO European Region, and found that taxation increases would result in decreases of cancer incidence and mortality, in line with the level of current taxation measured as a proportion of price ( Rovira et al, 2020 ).…”
Section: Discussionmentioning
confidence: 99%